2019
DOI: 10.1093/ecco-jcc/jjz088
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab Therapy is Ineffective for Primary Sclerosing Cholangitis in Patients With Inflammatory Bowel Disease: A GETAID Multicentre Cohort Study

Abstract: Background Whether vedolizumab may be effective as a treatment for primary sclerosing cholangitis [PSC] in patients with inflammatory bowel disease [IBD] remains controversial. Methods We performed a retrospective observational study of consecutive patients with IBD and PSC, treated with vedolizumab for at least 30 weeks in 22 centres of GETAID from January 2015 to June 2016. The outcomes included a decrease in the serum alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…34,46,51,53 A Jadad score ¼ 4 was assigned to the RCT. 42 Among the studies evaluated through the NOS scale there were four low (8.9%), 19,35,39,43 15 moderate (33.3%) 18,21,23,25,30,33,38,40,41,44,45,[47][48][49][50] and 25 high quality studies (55.6%) 4,20,22,24,[26][27][28][29]31,32,34,36,37,46,[51][52][53][54][55][56][57][58][59][60][61] ( Supplementary Material Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…34,46,51,53 A Jadad score ¼ 4 was assigned to the RCT. 42 Among the studies evaluated through the NOS scale there were four low (8.9%), 19,35,39,43 15 moderate (33.3%) 18,21,23,25,30,33,38,40,41,44,45,[47][48][49][50] and 25 high quality studies (55.6%) 4,20,22,24,[26][27][28][29]31,32,34,36,37,46,[51][52][53][54][55][56][57][58][59][60][61] ( Supplementary Material Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic approach was mainly based on clinical evaluation 4,[18][19][20][21][22][23][24][25]60 even if a considerable percentage of patients underwent biochemical and imaging tests. 4,19,[23][24][25][27][28][29][30][42][43][44][46][47][48][49][50][52][53][54][55][56][57][58][59][60][61] TNF inhibitors were the main biologic drugs for the treatment of EIMs and the response to therapy was primarily assessed through clinical data. Importantly, anti-TNF agents were confirmed to be effective in patients with EIMs, achieving a clinical response in over 50% of cases (except for PSC).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, it has been shown that active screening using MRCP in patients with There are studies underway to evaluate the efficacy of vedolizumab in patients with PSC, but results are controversial (22)(23)(24)(25). Despite an excellent safety profile, most of them fail to demonstrate a significant biochemical improvement of liver tests.…”
mentioning
confidence: 99%